4D CT image artifacts affect local control in SBRT of lung and liver metastases. (July 2020) - Sentker, Thilo; Schmidt, Vladimir; Ozga, Ann-Kathrin; Petersen, Cordula; Madesta, Frederic; Hofmann, Christian; Werner, René; Gauer, Tobias
Highlights: First study that correlates 4D CT image quality to clinical outcome. Retrospective study, based on 62 patients with 102 lung and liver metastases. 4D CT artifacts negatively influence outcome (multivariate analysis p < 0.05). Abstract: Background and purpose:  4D CT images often contain artifacts that are suspected to affect treatment planning quality and clinical outcome of lung and liver SBRT. The present study investigates the correlation between the presence of artifacts in SBRT planning 4D CT data and local metastasis control. Materials and methods:  The study includes 62 patients with 102 metastases (49 in the lung and 53 in the liver), treated between 2012 and 2016 with SBRT for mainly curative intent. For each patient, 10-phase 4D CT images were acquired and used for ITV definition and treatment planning. Follow-up intervals were 3 weeks after treatment and every 3–6 months thereafter. Based on the number and type of image artifacts, a strict rule-based two-class artifact score was introduced and assigned to the individual 4D CT data sets. Correlation between local control and artifact score (consensus rating based on two independent observers) were analyzed using uni- and multivariable Cox proportional hazards models with random effects. Metastatic site, target volume, metastasis motion, breathing irregularity-related measures, and clinical data (chemotherapy prior to SBRT, target dose, treatment fractionation) were considered as covariates. Results: Local recurrence was observed in 17/102 (17%) metastases. Significant univariable factors for local control were artifact score (severe CT artifacts vs. few CT artifacts; hazard ratio 8.22; 95%-CI 2.04–33.18) and mean patient breathing period ( > 4.8  s vs. ≤ 4.8  s; hazard ratio 3.58; 95%-CI 1.18–10.84). Following multivariable analysis, artifact score remained as dominating prognostic factor, although statistically not significant (hazard ratio 10.28; 95%-CI 0.57–184.24). Conclusion: The results support the hypothesis that image artifacts in 4D CT treatment planning data negatively influence clinical outcome in SBRT of lung and liver metastases, underlining the need to account for 4D CT artifacts and improve image quality.